2000
DOI: 10.1046/j.1464-410x.2000.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of bone fracture in patients receiving luteinizing hormone‐releasing hormone agonists for prostate cancer

Abstract: Objective To investigate the incidence of bone fractures in patients receiving luteinizing hormone-releasing hormone agonists (LHRH-a) for prostate cancer (in whom a continued low testosterone level after the long-term administration of these drugs reduces bone mineral density), and thus determine the risk of secondary osteoporosis. Between 1994 and 1999, 218 patients (mean age 77.3 years) were treated for o 6 months with LHRH-a for prostate cancer; of these, 14 (6%) had a bone fracture during their treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(61 citation statements)
references
References 9 publications
1
60
0
Order By: Relevance
“…21 Hatano et al, in a similar retrospective study over 5 years, reported a 6% incidence of fractures in men treated with ADT for Ͼ 6 months. 22 In the most detailed study to date, Oefelein et al found that 23 spinal fractures occurred in 181 men (12.7%) who were treated with ADT for 180 months, with 67% of the surviving men remaining free of fractures. 23 However, careful scrutiny of their data suggest that only 9 fractures could be attributed strictly to ADT.…”
Section: Fracture Rates In Men and Women Who Present With Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…21 Hatano et al, in a similar retrospective study over 5 years, reported a 6% incidence of fractures in men treated with ADT for Ͼ 6 months. 22 In the most detailed study to date, Oefelein et al found that 23 spinal fractures occurred in 181 men (12.7%) who were treated with ADT for 180 months, with 67% of the surviving men remaining free of fractures. 23 However, careful scrutiny of their data suggest that only 9 fractures could be attributed strictly to ADT.…”
Section: Fracture Rates In Men and Women Who Present With Osteoporosismentioning
confidence: 99%
“…fracture rates [21][22][23][24][25] have been reported in men with prostate carcinoma who are receiving ADT. Because many patients who present with prostate carcinoma are elderly and may have preexisting osteoporosis, subclinical vitamin D deficiency, or any of a multitude of medical problems, the risk of skeletal deterioration is increased.…”
mentioning
confidence: 99%
“…10,11 It is likely that this is related to the iatrogenic hypogonadism and resulting low serum testosterone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…9 Bone loss and fractures have been reported in these situations. 10,11 The side effect profile of LHRH agonists reflects the hypogonadal state that is produced. There is reduction in muscle mass, libido and potency as well as hot flushes, gynaecomastia, fatigue and weight gain, although the effect on skeletal homeostasis is less well known.…”
Section: Introductionmentioning
confidence: 99%
“…In a second study, 9% of 224 men treated with an LHRH agonist had a fracture over a median follow-up of 22 months; seven of these men had fractures resulting from osteoporosis, eight men from trauma, and five of mixed aetiology (Townsend et al, 1997). In a third study of 218 men, 6% had an osteoporotic fracture during 6 or more months treatment with anti-androgen therapy (Hatano et al, 2000); in a fourth study, 20% of 181 men treated for 10 years had osteoporotic fractures (Oefelein et al, 2001). Fracture rates were described in 429 men with prostate cancer treated by bilateral orchiectomy.…”
mentioning
confidence: 97%